O USO DA NANOTECNOLOGIA NO AGRONEGÓCIO: OS IMPACTOS CIENTÍFICO E TECNOLÓGICO - Junior, Edson Machado Fumagalli (2024)
The Brazilian agribusiness is one of the most important sectors of the global and national economy. Its success is partly due to the increasing agricultural productivity achieved by adopting various technologies. Nanotechnology, in particular, has enormous potential to impact the sector positively, motivating significant efforts and investments in research and development (R&D). Since nanotechnology applied to agribusiness is a recent research area, it is crucial to conduct studies on scientific production to better understand the ongoing advances and better direct national research initiatives. This study aimed to understand the current state of scientific research on nanotechnology for agribusiness, with a focus on Brazil's position. Bibliometrics and scientometrics were used as quantitative methods for information analysis to develop scientific indicators and patent research. Bibliographic records of scientific articles on nanotechnology for agribusiness published in the Web of Science and Lens.org databases were retrieved using the VOSviewer software for compiling information. Indicators were constructed to present publications by year, country, author, institution, and field of knowledge, detailing data for Brazil. In the analyzed period, 3,178 articles were retrieved from the Web of Science, with a limit of a thousand articles analyzed in detail, in addition to patent analysis on the Lens.org platform. The growth in scientific production over the years of the study was significant and consistent. The results indicate that the United States, India, and China are the leaders in research, with Brazil representing about 4.72% of the total publications (6th position). The analyses of authors and institutions reinforce the dominance of the United States and China in the area. Regarding Brazil, it is observed that most authors are linked to institutions located in the state of São Paulo, with emphasis on Embrapa and USP, indicating a certain centralization of research in the country. Concerning the fields of knowledge, on the Web of Science, publications are mainly concentrated in Nanotechnology and nanoparticles. On the Lens.org platform, where 93 patents were identified, the highlighted topics were pesticides, nanofertilizers, sensors and biosensors, food, and soil. This research aimed to conduct a technological prospecting of the use of nanotechnology in agribusiness through the analysis and review of scientific articles and patent applications. The results contribute to the construction of scientific knowledge in nanotechnology for agribusiness, with bibliometrics and scientometrics being valuable tools for quantifying scientific production in any field of knowledge. The study highlights the importance of conducting exploratory studies mobilizing different complementary databases to overcome the limitations of widely used information sources for analyzing scientific production.